Students’ Perception towards the Benefits of Teacher Feedback in their Writing Skill at English Education Department of Universitas Muhammadiyah Yogyakarta - Fidiyah Retno Wulandari (PBI 15 UMY 043, 2015)
*43 Writing is important yet difficult to be learned, thus teacher feedback is needed in the learning process in order to help students improve their writing skill. Teachers at English Education Department of Universitas Muhammadiyah often give feedback in their students’ writing, thus the researcher questions whether they take the benefits of it. The purposes of this study are to investigate students’ perception towards their writing skill, to investigate students’ perception toward their teachers’ feedback in the processes of learning writing, and to investigate students’ perception towards the benefits of teacher feedback in writing skill. The researcher used qualitative case study which was supported by semi-structure interview to collect the data. Convenience sampling was used to choose the participants. They were six students from batch 2011 who served as participants. Students who currently in their 8th semester have written some writing genres during their study thus they were compatible to serve as participants. There are four main findings in this research. Firstly, some students’ writing skill is in an intermediate level, the other students’ writing skill is improved, and the other students’ writing skill is good. Secondly, the participants mentioned the focuses of teacher feedback, types of teacher feedback, forms of teacher feedback, roles of teacher feedback, the effective teacher feedback, the favorite teacher feedback and their feeling towards teacher feedback. Thirdly, all participants took the benefits of teacher feedback in terms that teacher feedback improves students’ writing skill; it points out students’ weakness, error and difficulty; students learn from mistakes because of teacher feedback; students xi understand the error because of it; teacher feedback points out what aspect to improve; it improves grammatical skill; it improves writing concept; it improves students’ confidence; it improves critical and analytical thinking; it helps students avoid the same mistakes; students are aware to use conjunction because of teacher feedback; and it gives new information. The last is that students mentioned their routines dealing with the implementation of teacher feedback.